ANALISIS BAGI HASIL MUZARO’AH DALAM MENINGKATKAN PENDAPATAN PETANI KARET DI DESA SELAT KECAMATAN PEMAYUNG - Nova Wardana; Sissah Sissah; Maulana Hamzah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to find out whether the profit sharing for land cultivators and rubber plantation owners in Selat Village, Pemayung District, Batanghari Regency, Jambi Province is in accordance with the muzaro'ah profit sharing and to determine the impact of rubber farmers' profit sharing on the income of rubber farmers in Selat Village, Pemayung District, Regency. Batanghari, Jambi Province. This research method uses qualitative methods. The results of the research show that sharing the results of rubber from land cultivators with plantation owners has led to the rules of fiqh or procedures in Islamic economics because the profit sharing cooperation is carried out on a consensual basis without any coercion, profit sharing brings benefits in improving the welfare of the community, distribution of results which is carried out fairly in accordance with the provisions of Islamic law, there are no elements of fraud and taking advantage of opportunities in a tight situation. The suitability of the profit sharing between the land cultivator and the plantation owner is in accordance with the initial agreement as it is a mutual agreement, but there is no clarity on how long the agreement will last, causing deficiencies in the cooperation. An agreement without a time limit for the end of the contract agreement which allows for unilateral termination of the contract or failure to carry out the responsibilities of the land cultivator, resulting in a detrimental impact on one of the parties. Meanwhile, regarding the income from profit sharing, the people who work on the land think it has a good impact on their daily lives, it just depends on whether the price of rubber rises or falls.